Hidden Impacts of OER: Effects of OER on Instructor Ratings and Course Selection - Nusbaum, Amy T.; Cuttler, Carrie (Frontiers in Education, 2020)
One solution to the increasing cost of textbooks is open educational resources (OER). While previous studies have evaluated the effects of OER on student performance and perceptions of the material quality, few studies have evaluated other possible effects of OER. The goal of these studies was to examine whether the use of OER affects students' perceptions of instructors and whether students are more likely to select hypothetical courses using OER than courses using commercial materials. Results indicated that instructors assigned to use OER were rated more positively than those assigned a commercial textbook and students were more likely to select courses that had no course costs. These findings should motivate instructors and universities to adopt and advertise their OER use.